PREVALENCE OF T B IN THE TWO TRIBAL MANDALS OF SRIKAKULAM DISTRICT- A SURVEY - K. MYTHILI; KUM. V. JAYA KUMARI (The Bioscan, 2007)
Population stress, socioeconomic conditions and cultural changes ultimately bring about changes in the human environment, making it a paradise for infectious agents. Such stress on environment contaminates air, water, soil and food thus affecting our health. Srikakulam is coastal district in northern part of Andhra Pradesh. We have conducted a Survey on incidence of T B in two tribal mandals of Srikakulam i.e., Kotturu and Seethampeta for 2 yr. Out of every 1000, 2-10 people are affected by T B in India. But in these two mandals 129, 124 per every 1000 are suffering from T B The data was analyzed on the basis of poor hygienic environment, malnutrition, overcrowding conditions, socio-economic conditions of the people. The paper also focused on the relation between T B and HIV, T B and Diabetes.